2018
DOI: 10.1155/2018/8678267
|View full text |Cite
|
Sign up to set email alerts
|

6 O‐Galloylpaeoniflorin Attenuates Cerebral Ischemia Reperfusion‐Induced Neuroinflammation and Oxidative Stress via PI3K/Akt/Nrf2 Activation

Abstract: 6′-O-galloylpaeoniflorin (GPF), a galloylated derivative of paeoniflorin isolated from peony root, has been proven to possess antioxidant potential. In this present study, we revealed that GPF treatment exerted significant neuroprotection of PC12 cells following OGD, as evidenced by a reduction of oxidative stress, inflammatory response, cellular injury, and apoptosis in vitro. Furthermore, treatment with GPF increased the levels of phosphorylated Akt (p-Akt) and nuclear factor-erythroid 2-related factor 2 (Nr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 37 publications
(42 reference statements)
2
73
0
Order By: Relevance
“…Nrf2 activation can be controlled by the PI3K/AKT pathway [17,33]. S-propargyl-cysteine is reported to promote PI3K/AKT/Nrf2/HO-1 pathway activation, conferring an antioxidative effect to prevent from methionine and choline-deficient diet-induced NAFLD mice [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 activation can be controlled by the PI3K/AKT pathway [17,33]. S-propargyl-cysteine is reported to promote PI3K/AKT/Nrf2/HO-1 pathway activation, conferring an antioxidative effect to prevent from methionine and choline-deficient diet-induced NAFLD mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Nrf2 -/mice promoted the happening of more oxidative stresses that induced the evolution of NAFLD to NASH comparing with the WT mice [15]. Recent studies have shown that many small molecule compounds play the functions of anti-inflammatory, antioxidative stress, and antiapoptosis by activating PI3K/Akt/Nrf2 signal [16][17][18]. Some studies have found that S-propargyl-cysteine can protect MCD-induced fatty liver by the activation of Akt/Nrf2/HO-1 pathway [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic heart disease is a broader public health problem with increasing morbidity and high disability rate and mortality.Myocardial I/R injury, an inevitable secondary injury process of ischemic heart disease, is defined as the sudden restoration of blood flow in ischemic myocardium, which expands the death of myocardial cell and the infarction, and brings out the deterioration of cardiac function . Although a large number of experiments found that the mechanism of myocardial I/R injury may be connected with calcium overload, platelet aggregation, oxidative stress, and inflammatory factor, the specific pathogenesis is worthy of studying for exploring treatment targets of myocardial I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, GPF is better at scavenging 1,1-diphenyl-2-picrylhydrazine radicals than alpha-tocopherol. Our previous study showed that GPF can reduce neuroinflammation and cell damage after cerebral ischemia reperfusion by inhibiting oxidative stress responses [24]. However, whether GPF exerts anti-tumour effects has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%